Akidah Human Perfectness as a Concept of Dakwah - sabiruddin Juli (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2005)
There is a relation between human perfect ness and the concept of Muttaqun and Muflihun as Allah said that aqidah is a principle of human ife perfection. Exactly, iman is aqidah, good activities and the honesty. Iman is ofen called as amal saleh. that is every good activities that done for living in this earth or afler world. In other Words, it is good for spiritual and material point of view The writer concludes that people do not need to concentrate only one aspect. They should consider every Islamic aspects